What if employees brought their life to work? The relation of life satisfaction and work engagement - Gabriel, Carla (2020)
Previous research on work engagement has sought to understand the drivers, as well as the consequences, of engaging people at work. The drivers of engagement have been found mainly within the work domain. However, working life is not detached from personal life, which has been demonstrated by research on work-life balance. The goal of this research is to understand the relation between life satisfaction and work engagement. Data were collected from a sample of 571 employees from major Portuguese companies using a questionnaire. The results confirmed the constructs used, and the regression model showed that life satisfaction is related to work engagement. The main conclusion was that work engagement can be explained by factors external to the organization, which are an integral part of employees’ lives. Being a psychological and emotional state, work engagement can be related to other aspects of employees’ lives besides their organizational and job roles.